Kegagalan Penerapan Asas Itikad Baik dalam Praktik Fake Reviews pada Transaksi E-Commerce Berdasarkan Analisis Sistem Hukum Lawrence M. Friedman - Siti Alya Cantika Nurjihan (Letterlijk, 2026)
The development of electronic commerce (E-Commerce) has transformed the way people conduct transactions by utilizing digital systems as a medium for information exchange and contract formation. One of the emerging phenomena in electronic transactions is the practice of fake reviews, which are used to influence consumers' perceptions of products or services. This practice has the potential to violate the principle of good faith because it provides information that does not reflect actual conditions and may mislead consumers in the decision-making process. This study aims to analyze the failure of the implementation of the principle of good faith in the practice of fake reviews in E-Commerce transactions based on Lawrence M. Friedman’s legal system theory. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that, normatively, the principle of good faith is regulated under Article 1338 paragraph (3) of the Indonesian Civil Code and is further supported by the provisions of the Consumer Protection Law. However, the implementation of this principle has not been effective due to weaknesses in the legal substance, which does not specifically regulate fake reviews, the legal structure, which has not optimally carried out supervision and law enforcement, and the legal culture of society, which remains permissive toward the manipulation of digital reviews. Therefore, strengthening regulations, enhancing oversight of E-Commerce platforms, and increasing public legal awareness are necessary to ensure consumer protection and justice in digital transactions.